Effects of the Participative Management Program on Outcome of Clinical Nursing Practice Guideline Usage for Sepsis Patients among Professional Nurses in a Tertiary Level Hospital - Sakulrat, Pornpen; Sritoomma, Netchanok; Aree, Patcharaporn (NU Journal of Nursing and Health Sciences, 2023)
The quasi-experimental research aimed to study the effects on outcomes of the use of the participatory management program of clinical nursing practice guideline for sepsis patients. The sample consisted of 60 professional nurses who worked in in-patient units, divided in 30 people for experimental group and 30 people for control group, by using a purposive sampling. The research instruments comprised the participatory management programs and a questionnaire for the outcomes from the use of clinical nursing practice guideline for sepsis patients. The content validity index of the questionnaire was 0.97 and the Cronbach’s alpha coefficient was 0.92. Data were analyzed by using descriptive statistics and Paired t-test, independent t-test.The results indicated that after receiving the program, for the nursing practice part, an average score in the experimental group was higher than before the trial with statistically significant (p<.05) and the experimental group also had an average score for using the nursing practice guidelines for sepsis patients was significantly higher than the control group (p<.05). An average score of the experimental group was at the highest level ( = 4.59, S.D. =.26) during an average score of the control group was at the moderate level ( = 3.23, S.D. =.41). For the patient outcome part, when compared before and after receiving the program, the experimental group had the mortality rate significantly different (p<.05). When compared between the experimental group and the control group found that the rate of patient transfer to the intensive care unit and an average of length of stay were not significantly different (p>.05). Yet, when compared before and after receiving the program, it revealed that the mortality rate, the rate of patient transfer to the intensive care unit, and an average of length of stay were all decline. It demonstrated that this program could lead to the positive outcomes in nursing practice for sepsis patients.